Can Persistent Offenders Help Us Understand Desistance from Crime? - Kang, Timothy (Journal of developmental and life-course criminology, 2022)
There is abundant evidence that desistance from crime is a process rather than an event and that it is often linked to specific life events (e.g., marriage, employment) and shifts in cognition and identity (Giordano et al., 2002; Loughran et al., 2017; Maruna, 2001; Sampson & Laub, 1993). The processual nature of desistance acknowledges that fact that individuals don’t immediately quit committing crimes but rather they can slow down, and even have relatively long periods abstaining from crime, before offending again (Laub & Sampson, 2003, p. 54; Bushway et al., 2001). Given this heterogeneity in offending patterns, we seek to determine what processes are responsible for an upturn in offending when an individual seems to be committed to long-term desistance? What are the immediate life circumstances and subjective appraisals that underpin a resurgence in offending? Using a sample of persistent offenders, we aim to shed new light on desistance research by considering how offenders depicted their own cognitive shifts that suggested they were on the road to recovery and the factors that caused them to fail to achieve it.